2020
DOI: 10.1186/s12911-020-01227-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of most influential co-occurring gene suites for gastrointestinal cancer using biomedical literature mining and graph-based influence maximization

Abstract: Background: Gastrointestinal (GI) cancer including colorectal cancer, gastric cancer, pancreatic cancer, etc., are among the most frequent malignancies diagnosed annually and represent a major public health problem worldwide. Methods: This paper reports an aided curation pipeline to identify potential influential genes for gastrointestinal cancer. The curation pipeline integrates biomedical literature to identify named entities by Bi-LSTM-CNN-CRF methods. The entities and their associations can be used to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A bulk of omics data from diverse databases including TCGA (The Cancer Genome Atlas), the ICGC (The International Cancer Genome Consortium), the PCAWG (The Pan-Cancer Analysis of Whole Genomes), and TARGET (Therapeutically Applicable Research to Generate Effective Treatments) have shown that carcinogenesis-driving genes were prone to gene alterations in a wide range of all known cancer types. , This occurs ubiquitously, especially for tumor suppressor genes and proto-oncogenes, including TP53, PIK3CA, KRAS, PTEN, CDKN2A, EGFR , and BIM . , These genes exhibit single-gene mutations or combined mutations of multiple genes during carcinogenesis and progression, which poses a great challenge to the current cancer therapies. …”
Section: Introductionmentioning
confidence: 99%
“…A bulk of omics data from diverse databases including TCGA (The Cancer Genome Atlas), the ICGC (The International Cancer Genome Consortium), the PCAWG (The Pan-Cancer Analysis of Whole Genomes), and TARGET (Therapeutically Applicable Research to Generate Effective Treatments) have shown that carcinogenesis-driving genes were prone to gene alterations in a wide range of all known cancer types. , This occurs ubiquitously, especially for tumor suppressor genes and proto-oncogenes, including TP53, PIK3CA, KRAS, PTEN, CDKN2A, EGFR , and BIM . , These genes exhibit single-gene mutations or combined mutations of multiple genes during carcinogenesis and progression, which poses a great challenge to the current cancer therapies. …”
Section: Introductionmentioning
confidence: 99%
“…Scientific articles provide text mining (TM) applications in cancer biology ( Zhu et al, 2013 ; Azam et al, 2019 ; Wang et al, 2020 ). Several solutions are currently available to meet the growing need for different cancer gene panels.…”
Section: Introductionmentioning
confidence: 99%